2015
DOI: 10.14221/ajte.2015v40n6.2
|View full text |Cite
|
Sign up to set email alerts
|

Teachers´ Practices and Mental Models: Transformation Through Reflection on Action

Abstract: This contribution explores the relationship between teaching practices, teaching discourses and teachers´ implicit representations and mental models and the way these dimensions change through teacher education (T.E). In order to study these relationships, and based on the assumptions that representations underlie teaching practices and that T.E might affect these representations, a T.E course was designed and implemented in Argentina. The course focused on teacher intervention in personal narrative telling in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
0
7
0
3
Order By: Relevance
“…Similar suggestions have been made previously by Cropley, Miles, and Peel (2012) who suggested that reflective practice would only be effective if the approach adopted suited the individual coach in question. shared conversational practices with peers or others (Dixon et al, 2013;Huntley & Kentzer, 2013;Knowles et al, 2007;Manrique & Sanchez Abchi, 2015). It is proposed that such shared approaches afford opportunity for facilitation of 'levelness', and thus more critical reflective practice (Knowles & Gilbourne, 2010).…”
mentioning
confidence: 99%
“…Similar suggestions have been made previously by Cropley, Miles, and Peel (2012) who suggested that reflective practice would only be effective if the approach adopted suited the individual coach in question. shared conversational practices with peers or others (Dixon et al, 2013;Huntley & Kentzer, 2013;Knowles et al, 2007;Manrique & Sanchez Abchi, 2015). It is proposed that such shared approaches afford opportunity for facilitation of 'levelness', and thus more critical reflective practice (Knowles & Gilbourne, 2010).…”
mentioning
confidence: 99%
“…Asumiendo que el campo de la investigación sobre los cambios y las implicaciones que el docente tiene en el aula cuando aplica la práctica reflexiva es escaso y limitado (Camburn, 2010;Charteris, 2015;Cirocki et al, 2014;Lupinski et al, 2012;Manrique y Abchi, 2015), esta investigación pretende ampliar el conocimiento en esta dirección. La evaluación realizada de la experiencia piloto confirma que Pensadero de maestros es un proyecto que promueve la formación continua de los docentes.…”
Section: Ejecución Y Consolidaciónunclassified
“…Con el fin de seguir desarrollando el concepto de práctica reflexiva y las dinámicas que la desarrollan en la profesión docente se hace necesario realizar nuevas investigaciones en este campo (Camburn, 2010;Charteris, 2015;Cirocki et al, 2014;Hickson, 2011;Lupinski et al, 2012;Manrique y Abchi, 2015;Tan, 2008). Sería positivo ampliar las herramientas de recogida de información, usando cuestionarios, y la muestra, implementando el proyecto en realidades y contextos diversos como son los Institutos de Educación Secundaria o contextos socioeconómicos diferentes, con el fin de consolidar y ampliar los datos obtenidos en la investigación aquí presentada.…”
Section: Ejecución Y Consolidaciónunclassified
“…The assumption underlying this study was that each teacher holds an idiosyncratic mental model for teaching -a hidden, dynamic psychological entity that organizes the way he or she understands (Lynam & Brown, 2012;Manrique & Abchi, 2015;Mevorach & Strauss, 2012). This model is activated (in-action) while they are teaching.…”
Section: Literature Reviewmentioning
confidence: 99%